2021
DOI: 10.18421/tem101-26
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Strategic Management Program: Context, Input, Process, Product Model as a Prototype for Business Academies

Abstract: The present study examines the evaluation models of strategic management (SM) programs in business academies and evaluates a sample program based on Stufflebeam's context, input, process, product (CIPP) program evaluation model. When evaluation studies used in Turkey were scrutinized, Stake's countenance model and Provus's discrepancy model were also discovered; however, the CIPP Model has generally been used. Further, this study explores (1) the history of SM education and (2) SM education within the perspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…CIPP is a four-stage review that includes context evaluation, input evaluation, process evaluation, and product evaluation. In the legal framework, the CIPP is explained in Table IV as it follows (Birgili & Kırkıç, 2021): This evaluation is focusing on the organization's readiness in implementing the SOP, by analyzing the technical equipment, personnel capabilities, and management system in conducting the passport issuance process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CIPP is a four-stage review that includes context evaluation, input evaluation, process evaluation, and product evaluation. In the legal framework, the CIPP is explained in Table IV as it follows (Birgili & Kırkıç, 2021): This evaluation is focusing on the organization's readiness in implementing the SOP, by analyzing the technical equipment, personnel capabilities, and management system in conducting the passport issuance process.…”
Section: Discussionmentioning
confidence: 99%
“…Product evaluation to help further decisions, what results have been achieved product evaluation to help make further decisions, both regarding the results that have been achieved and what to do after the program runs by analyzing the implementation of the Standard Operational Procedures (SOP) in on the Process on conducting the new passport issuance process number: IMI-GR.01.01-1102 using the Customer Satisfaction Index (IKM) as the main indicator. Source: Authors analysis, CIPP for the legal studies (Birgili & Kırkıç, 2021;Hakan & Seval, 2011).…”
Section: Product Evaluationmentioning
confidence: 99%
“…( 5) Sports coaching and development is carried out through family channels, education channels, and community channels based on the development of sports for all people which lasts a lifetime. (6) The coaching and development of sports as referred to in paragraph (5) aims to: a) form a character; b) provide basic knowledge of sports; c) improve the degree of fitness and health; and d) creating healthy and active lifestyle habits throughout life.…”
Section: The Purpose Of Coaching Programmentioning
confidence: 99%
“…Ramadhan, et al, (2020) [25] revealed that the development of national sports can be done as well as possible, the necessary components and components are (1) target-oriented, (2) management, (3) energy, (4) athletes, (5) facilities and infrastructure , (6) program structure and content, (7) learning resources, (8) methodology, (9) evaluation and research, and (10) funding. The same thing was expressed (Lubis, et al, 2017) that the components in the national sports coaching system are: (1) goals, (2) management, (3) manpower factors, (4) athletes, (5) facilities and infrastructure, (6) program structure and content, (7) learning resources, (8) methodology, (9) evaluation and research, and (10) funding. The success of developing a systemic, integrated, directed and programmed athlete achievement can clearly be seen from several influencing factors, namely: (1) Availability of sufficient potential athletes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation